Green School Initiatives: Cultivating Environmental Awareness in Elementary Education - Baharuddin S, Ahmad; Saihan, Saihan; Usriyah, Lailatul (Journal of Educational Research and Practice, 2025)
This study aims to describe the implementation of environmental care character education at SD Darus Sholah Jember, identify the challenges encountered in instilling environmental care character values through applying green school principles, and explain the efforts made to overcome these challenges. This research employs a qualitative descriptive approach, utilizing primary and secondary data. Primary data were obtained through interviews with the school principal, teachers, and students in grades III and IV, while secondary data consisted of documents related to environmental care character education. The data collection methods included observation, interviews, and documentation, which were analyzed using data reduction, data display, and conclusion-drawing techniques. Data validity was ensured through source and technique triangulation. The research findings indicate that environmental care character education at SD Darus Sholah Jember is implemented through several measures: (1) curriculum development encompassing self-development programs, integration of environmental care values into subjects, fostering a school culture of environmental care, improving the learning process, and managing school environmental health; (2) challenges faced include students' poor habits in maintaining cleanliness, low awareness of proper waste management, and technical issues such as inadequate water flow; (3) efforts to address these challenges involve providing students with understanding and guidance on maintaining personal hygiene, strengthening interactions between teachers and parents, and establishing collaborations with school alums.